THE ROLE OF SUBAK AS CULTURE CAPITAL TO DEVELOP COMMUNITY BASED TOURISM VILLAGE (CASE STUDY IN PINGE VILLAGE, BALI PROVINCE, INDONESIA) - Ni Putu Nina Eka LESTARI; Made Kembar Sri BUDHI; I Made SUIDARMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The city of Plovdiv in Bulgaria was elected by the European Commission to be the European Capital of Culture for 2019. Plovdiv is a city with eight thousand years of history located on one of the most fertile plains in Europe - the vast plain of Thrace, inhabited for thousands of years by various tribes and peoples. Eight civilizations and cultures inhabited the city: Prehistoric, Thracian, Macedonian, Roman, Byzantine, Old Bulgarian, Ottoman, Renaissance and contemporary culture. They left a rich, unique and priceless cultural heritage. For centuries in Plovdiv there have been living together Orthodox, Catholic, Muslim, Jewish, Armenian and other communities. Therefore the city has a rich variety of religions and remarkable monuments of the different religious cultures and cults. The subject of the present study is the state of cultural and historical tourism in the city of Plovdiv. The period 2015-2017 has been examined. The data required for the study are taken from the statistical reports. In 2017 a survey was conducted among 120 tourists during the seasons: spring, summer and autumn. The purpose of the survey was to determine the state of cultural and historical tourism in the city of Plovdiv. Moreover, for the purpose of the study a working group of 10 experts has been set up - experts in areas relevant to the development of cultural tourism in the city of Plovdiv. Each of the experts makes suggestions about the circumstances, conditions and factors on which the further development of cultural tourism in the city of Plovdiv depends. In this way, the assessment of both the experts in this sector and the users of this tourist product has been established. A SWOT analysis of the strengths and weaknesses of cultural and historical tourism in the city of Plovdiv has been carried out.